Perancangan Tahap Pra-Produksi Dalam Produksi Video Stop Motion: Desain Komunikasi Visual - Aisyah Zahwah Andrasari; Widyasari Widyasari; Bayu Setiawan (Jurnal Publikasi Ilmu Komputer dan Multimedia, 2026)
Stop motion technique is a combination of photos taken sequentially to create the illusion of movement. Stop motion video is also able to increase visual appeal and also strengthen the delivery of the message contained to the audience. This study aims to design and produce audio-visual works based on stop motion animation techniques with a pixilation approach that raises the theme of "going home". The method used includes the stages of designing audio-visual works, namely pre-production, production, and post-production. In the pre-production stage, the synopsis, storyline, storyboard, and technical planning are prepared. The design results show that careful planning in the pre-production stage is able to provide clear direction in the production process, minimize technical errors, and increase the effectiveness of teamwork. The application of pixilation techniques as part of stop motion provides unique visual power in displaying emotions and symbolization of the story. Overall, the resulting work is able to convey the message about the meaning of "going home" as an emotional space that is always present for individuals, while also showing that systematic planning plays an important role in producing maximum audio-visual works.